2019
DOI: 10.1177/1043454219874007
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of Young Children With Cancer and Their Parents With Nurses’ Caring Practices During the Cancer Trajectory

Abstract: Children with cancer require repeated hospitalizations and the family’s everyday life and routines undergo change. Concrete descriptions of how nurses act when caring for children with cancer throughout the various phases of care and treatment are sparsely highlighted in the literature. The aim of this study was to describe young children with cancer and their parents’ experiences of nurses’ caring practices over a 3-year period, from diagnosis to follow-up. This study is based on semistructured interviews wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
15
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 60 publications
0
15
0
4
Order By: Relevance
“… 85 , 86 Other factors were related to health care providers, with nurses being especially important. 87 , 88 As it relates to physicians, studies highlighted the importance of honest, complete communication with patients about prognosis. 83 , 89 , 90 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… 85 , 86 Other factors were related to health care providers, with nurses being especially important. 87 , 88 As it relates to physicians, studies highlighted the importance of honest, complete communication with patients about prognosis. 83 , 89 , 90 …”
Section: Resultsmentioning
confidence: 99%
“…Factors found to increase perseverance of pediatric and AYA cancer patients were: the cancer experience, 34 , 167 hope for a future cure, 168 and relationships with oncology nurses. 87 The cancer experience was described as giving patients an “unknown strength” by patients, 167 whereas hope for a cure allowed patients to persevere despite treatment side effects. Finally, perseverance was described as an active choice in the face of disease progression.…”
Section: Resultsmentioning
confidence: 99%
“…However, it does not decrease. Parents have stated that even though they felt knowledgeable about their child's illness, they still wanted the information to be repeated in order to gain more in-depth knowledge (Enskär et al, 2020;McGrath et al, 2007;Ringnér et al, 2011). Parents found having repeated planned information meetings and access to written information they could return to over time was helpful during the treatment trajectory (Enskär et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Parents have stated that even though they felt knowledgeable about their child's illness, they still wanted the information to be repeated in order to gain more in-depth knowledge (Enskär et al, 2020;McGrath et al, 2007;Ringnér et al, 2011). Parents found having repeated planned information meetings and access to written information they could return to over time was helpful during the treatment trajectory (Enskär et al, 2020). Studies have shown that transitions between phases of the treatment increase parental uncertainty, and that the discharge from hospital and end of treatment are particularly challenging (Gunter and Duke, 2019;McGeehin Heilferty, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Nurses adoption of pain-relieving measures depended on their experiences in dealing with pain and their convictions about pain. Nurses are expected to assess children using developmentally appropriate strategies(Enskär et al, 2020). With these competencies at hand, nurses will be able to develop a deeper understanding of the patient as a unique individual.Participants mentioned that they provided a hopeful fight, by giving holistic care which included giving education on cancer to clients and their family members.…”
mentioning
confidence: 99%